Du déchet au Technosol fertile : l’approche circulaire du programme français de recherche SITERRE - Laure Vidal-Beaudet (VertigO)
The national research program (SITERRE, 2011-16) funded by the French Environmental Agency (ADEME) was dedicated to the construction of soils with urban wastes for city greening, as an alternative to the consumption of natural resources (agricultural earth and quarry stones). The objectives of the program were to : (1) express the expected properties of soils that could fulfil optimally the main green area land-uses in terms of fertility, bearing capacity and environmental impacts, (2) define relevant indicators of the soil fertility and the expected quality for constructed soils, (3) propose constructed soil design profiles linked with land-uses, (4) identify and report the wastes that may be suitable for soil construction,(5) evaluate soil agronomic properties evolution under in situ conditions, and (6) check the safety of the mixtures for the environment and the health of the inhabitants. The organic and mineral waste mixtures designed and tested to follow constructed soil during the SITERRE project, are efficient to develop alternative fertile soils with relevant physico-chemical properties ensuring root development. Their safety for the environment and human health has been verified. To develop urban horticulture, it is essential to educate all the city makers about optimal soil specifications expected for urban soils and how to establish sustainable soil management. The Technosols construction proposed by the SITERRE program must follow a precise protocol and call on expert appraisals to provide fertile soils.The results of the work, published in a book (Damas and Coulon, 2016) should now help to develop an efficient decision support system for urban landscape managers.